2021
DOI: 10.5213/inj.2040326.163
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Botulinum Toxin Injection for Refractory Enuresis Based on Urodynamic Assessment

Abstract: This study aimed to determine the urodynamic characteristics of refractory enuresis and explore whether they can be managed through differential endoscopic injection with botulinum toxin. Methods: A total of 27 patients with nonmonosymptomatic enuresis who showed no response after conservative treatment for more than 12 months were included herein. Patients then underwent videourodynamic study and received a differential endoscopic injection of botulinum toxin within the same day. Reduced capacity, detrusor ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…According to a recent study, unlike MNE, lower urinary tract dysfunction and NMNE were correlated with constipation 23 . The association between MNE and constipation previously postulated in the literature may have resulted from the lack of distinction between MNE and NMNE, since the latter is frequently associated with constipation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to a recent study, unlike MNE, lower urinary tract dysfunction and NMNE were correlated with constipation 23 . The association between MNE and constipation previously postulated in the literature may have resulted from the lack of distinction between MNE and NMNE, since the latter is frequently associated with constipation.…”
Section: Discussionmentioning
confidence: 93%
“…In Tolunay et al's study only four out of 27 patients with NMNE had normal urodynamic results (7.4%), while 16 (59.3%) had overactive detrusors 18 . According to Jung et al, more than half of their NMNE patients who had preoperative diagnoses of overactive bladder (OAB) or dysfunctional voiding had different urodynamic diagnosis 23 . Considering that the treatment of NMNE involves treating both lower urinary tract symptoms (LUTS) and enuresis, it is important to note that LUTS involves heterogeneous urodynamic abnormalities.…”
Section: Discussionmentioning
confidence: 97%
“…In severely therapy-resistant enuresis, the endoscopic injection of botulinum toxin and sacral neurostimulation have been studied as alternative treatments, even if they are not recommended as first- and second-line treatments because of the lack of evidence and randomized clinical trials. A pilot study by Jung et al including 27 patients with NME, who showed no response after conservative treatment for more than 12 months, documented an improvement of detrusor overactivity after intravesical botulinum toxin injection up to one year later, while Hoebeke et al reported positive long-term results in 70% of children after a single injection [ 81 , 82 ]. There are limited data on the effectiveness of sacral nerve stimulation in children.…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are two theories about bladder function derangements. One is bladder detrusor hyperactivity, embodying some children with enuresis who can be treated with oral anticholinergic drugs or intravesical injection of botulinum toxin (70) and a great overlap between nocturnal enuresis and urgent urinary incontinence (71,72). The other is reduced bladder functional capacity (BFC) (73, 74).…”
Section: Pathogenesismentioning
confidence: 99%